3He spin-echo scattering indicates hindered diffusion of isolated water molecules on graphene-covered Ir(111) - Kyrkjebø, Signe; Cassidy, Andrew; Lambrick, Sam; Jardine, Andrew; Holst, Bodil; Hornekær, Liv (Frontiers in Chemistry, 2023)
The dynamics of water diffusion on carbon surfaces are of interest to fields as diverse as furthering the use of graphene as an industrial-coating technology and understanding the catalytic role of carbon-based dust grains in the interstellar medium. The early stages of water-ice growth and the mobility of water adsorbates are inherently dependent on the microscopic mechanisms that facilitate water diffusion. Here, we use 3 He spin-echo quasi-inelastic scattering to probe the microscopic mechanisms responsible for diffusion of isolated water molecules on graphenecovered and bare Ir(111). The scattering of He atoms provides a non-invasive, highly surfacesensitive means by which to measure the rate at which absorbates move around on a substrate at very low coverage. Our results provide an approximate upper limit on the diffusion coefficient for water molecules on GrIr(111) of < 10 −12 m 2 /s, an order of magnitude lower than the coefficient which describes the diffusion of water molecules on the bare Ir(111) surface. We attribute the hindered diffusion of water molecules on the GrIr(111) surface to water trapping at specific areas of the corrugated moir é superstructure. Lower mobility of water molecules on a surface is expected to lead to a lower ice nucleation rate and may enhance the macroscopic anti-icing properties of a surface.